Perbandingan Kebijakan Pemerintah Indonesia dan Thailand dalam Mengendalikan Kondisi Beras Akibat Fenomena El-Nino 2023 - Fajar, Moch. Malik; Rahmah, Fania Jamilatul; Atika, Sitti Nurmahida; Saputro, Riro Adnan; Appandi, Karlina; Alzira, Riva; R, Rudiana (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The El-Nino phenomenon causes long droughts in several parts of the world. Indonesia and Thailand are the countries with the worst impact of El-Nino. This has an impact on stabilizing the national rice stocks of the two countries. Indonesia and Thailand are the largest rice producing countries in Southeast Asia. The El-Nino phenomenon means that both countries must anticipate and handle it through government policies. The policies issued by the government will determine success in stabilizing national rice stocks. The policies issued by Indonesia and Thailand have differences and similarities. Despite this, many Indonesian policies are still less effective and efficient. Comparing the policies of two countries in dealing with national rice stocks will show the strengths and weaknesses of each policy, so that policies can be analyzed and evaluated in the future.